Increasing Social Presence in Online Learning through Small Group Discussions - Akcaoglu, Mete; Lee, Eunbae (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Social presence is a difficult to achieve, but an imperative component of online learning. In this study, we investigated the effect of group size on students' perceptions of social presence in two graduate-level online courses, comparing small group versus whole class discussions. Our results indicated that when in small group discussions, students perceived a higher level of social presence in terms of sociability, t(32) = 3.507, p = .001; social space, t(29) = 3.074, p = .005; and group cohesion, t(32) = 3.550, p = .001. We discuss how placing students in small and permanent discussion groups can augment social presence. Designers and educators of online learning can strategically modify group size to promote social presence in asynchronous online discussions.